THE ANALYSIS OF ELECTRONIC WORD OF MOUTH, DESTINATION IMAGE, AND VISITING DECISION ON SATISFACTION - Kurniawan, Muhammad Arif; Maftukhah, Ida (Universitas Negeri Semarang, 2020)
The purpose of this study was to find out the influence of electronic word of mouth and destination image on satisfaction through the visiting decision to the visitors of Banjarejo Tourism Village. The population in this study were all visitors of the Banjarejo Tourism Village. The total of samples was 120 respondents with incidental sampling techniques through a Likert scale questionnaire. The data collection method used a questionnaire. Data analysis used classical assumption test and hypothesis test (t-test and path analysis) with SPSS 25 statistical version. The results showed that electronic word of mouth had a positive influence and significant on visitor satisfaction, destination image had a positive influence and significant on visitor satisfaction, visiting decision had a positive influence and significant on visitor satisfaction, and the visiting decision mediated the influence of electronic word of mouth and destination image on visitor satisfaction.